2021
DOI: 10.3390/ani11041054
|View full text |Cite
|
Sign up to set email alerts
|

Association of Body Condition Score and Score Change during the Late Dry Period on Temporal Patterns of Beta-Hydroxybutyrate Concentration and Milk Yield and Composition in Early Lactation of Dairy Cows

Abstract: Monitoring the body condition score (BCS) of dairy cows is a management strategy that can assist dairy producers in decision-making. The BCS and its variations reflect the level of body fat reserves and fat mobilization throughout the different stages of lactation. Cows that mobilize excessive amounts of fat reserves in response to the increased energy requirements of the transition period are more likely to have higher beta-hydroxybutyrate (BHB) concentration in blood, leading to a higher incidence of hyperke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…Low BCS in the prepartum period has been directly linked to the development of RTD 38 . Excessive BCS loss from the dry period to early lactation has been associated with poor health in early lactation, including an increased incidence of metritis, RFM and hyperketonaemia 39–41 . Limitations in data collection meant that loss of BCS between dry off and lactation was not analysed in the present study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Low BCS in the prepartum period has been directly linked to the development of RTD 38 . Excessive BCS loss from the dry period to early lactation has been associated with poor health in early lactation, including an increased incidence of metritis, RFM and hyperketonaemia 39–41 . Limitations in data collection meant that loss of BCS between dry off and lactation was not analysed in the present study.…”
Section: Discussionmentioning
confidence: 97%
“…38 Excessive BCS loss from the dry period to early lactation has been associated with poor health in early lactation, including an increased incidence of metritis, RFM and hyperketonaemia. [39][40][41] Limitations in data collection meant that loss of BCS between dry off and lactation was not analysed in the present study. Changes between body condition at calving and 43 ± 3 DIM were not associated with UDE, indicating that these measures of body condition alone are not useful when considering the risk factors for UDE.…”
Section: Discussionmentioning
confidence: 99%
“…Perinatal cows often encounter oxidative stress, which may cause host immune and inflammatory dysfunction, thus, endangering the health and reducing milk production of dairy cows (Bendich, 1993; Sordillo & Aitken, 2009). BCS is a recognised tool for evaluating body fat mobilisation of dairy cows (Rodriguez et al, 2021). It has been reported that the BCS of dairy cows was decreased during the perinatal period (Y. Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A study revealed a positive association between the body condition at calving and an increase in the concentration of BHB during early lactation [60,61]. [3] also found an increase in the concentration of BHB in the first 14 days of lactation in milk cows with body condition ≥ 4 points compared to cows with body condition ≤ 3.75 points according to 1-5 point scal at day 21 of the expected date of calving. After calving, there are two correlated factors: decreased feed intake and increased fat mobilization.…”
Section: Relationship Of Body Condition Score With Some Blood Metabol...mentioning
confidence: 95%
“…Most of the high-production milk cows suffer from a state of negative energy balance, especially during early lactation, because the energy requirements to maintain the functions of body tissues and production exceed what the cows consume of energy, and with increased production, the metabolic rate rises, which is reinforced by an increase in metabolic stress, and then followed by a decline in reproductive characteristics And health status [1,2,3,4], and mobilizing the body's energy reserves during early production enables the cow to bridge the gap between dietary energy intake and its deficiency at production (5). The changes in energy reserves have a significant impact on the health condition and reproductive performance in milk cows, so here it is clear that it is necessary to use administrative means to monitor the energy reserves in the cow's body.…”
Section: Introductionmentioning
confidence: 99%